Comparison of the use of prenatal care services and the risk of preterm birth between pregnant women with disabilities and those without disabilities: A nationwide cohort study - Meng-Bin Tang; Meng-Bin Tang; Meng-Bin Tang; Pei-Tseng Kung; Pei-Tseng Kung; Li-Ting Chiu; Wen-Chen Tsai (Frontiers Media S.A., 2023)
ObjectiveThe difficulties faced by pregnant women with disabilities in accessing health care may make them less likely to receive prenatal care. The aims of this study were to compare the number of prenatal services and the risk of preterm birth between pregnant women with and without disabilities.MethodsA total of 2999 pregnant women aged ≥20 years with birth records in 2011-2014 in Taiwan were enrolled. Data were obtained from the Registration File for Physical and Mental Disabilities and the National Health Insurance Research Database. A 1:4 matching between pregnant women with disabilities and those without disabilities was performed. The logistic regression analysis with generalized estimating equations was used to analyze.ResultsThe median of prenatal care services used by pregnant women with disabilities was 9.00 (interquartile range, IQR: 2.00). Pregnant women with disabilities used fewer services than those without disabilities (median, 10.00; IQR: 1.00). The disabled group (8.44%) had a significantly higher proportion of preterm births than did the non-disabled group (5.40%). The disabled group was at a 1.30 times higher risk of preterm births than was the non-disabled group.ConclusionsPregnant women with disabilities used significantly fewer prenatal care services and had a significantly higher risk of preterm birth than pregnant women without disabilities.